Player in the league of the damned – ghettos in modern Germany and their representations in works of Feridun Zaimoglu - Wesołowska, Olga (Migracja w języku, literaturze i kulturze, 2020)
Migration in modern world affects ghettoization. Also Germany is struggling with this problem, especially in urban areas. Immigrant neighborhoods are becoming districts which are often described as ghettos. And only do they have their own rules, but also own language – a kind of sociolect. The aim of this article is to analyze the representations of contemporary German ghettos in works of Feridun Zaimoglu (based on his novels Kanak Spark and Koppstoff).